The Influence of Job Placement and Career Development on Employee Performance at Bank Sumsel Babel Sub Branch KM 12 Palembang - Fitriani, Hikmah; Marnisah, Luis; Roswaty, Roswaty (International Journal of Marketing & Human Resource Research, 2024)
The purpose of this study was to test whether work placement and career development have a positive effect on employee performance at Bank Sumsel Babel Sub-Branch KM 12 Palembang City. The sampling technique in this study was saturated sampling, which took the entire sample of 25 respondents who were employees of Bank Sumsel Babel Sub-Branch KM 12 Palembang. This research method uses multiple linear regression analysis methods. The results showed that job placement and career development partially and simultaneously had a positive effect on employee performance.